2000
DOI: 10.1614/0890-037x(2000)014[0402:ddniyi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diclosulam Does Not Influence Yields in Eight Virginia Market-Type Peanut (Arachis hypogaea) Cultivars1

Abstract: Field studies were conducted in 1996 and 1997 to evaluate response of eight peanut cultivars to diclosulam applied preplant incorporated at 36 g ai/ha in a weed-free environment. Peanut cultivars evaluated included ‘NC 12C’, ‘NC 7’, ‘VAC 92R’, ‘NC-V 11’, ‘NC 10C’, ‘AT VC 1’,‘NC 9’, and the experimental breeding line N90010E. Visible injury 3 wk after planting was less than 5% regardless of cultivar. No injury was observed at 21 d after planting. Diclosulam did not influence the incidence of early leaf spot, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 9 publications
5
31
0
Order By: Relevance
“…In previous research, only POST applications of chlorimuron had an influence on the incidence of TSWV in peanut (Prostko et al 2009). In other peanut research, applications of diclosulam (PPI), flumioxazin (PRE), imazapic (POST), paraquat (POST), and 2,4-DB (POST) did not affect the incidence of TSWV (Bailey et al 2000;Faircloth and Prostko 2010;Tubbs et al 2010;Wilcut et al 2001). The mechanism of how certain herbicides influence TSWV in peanut has not yet been discovered.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research, only POST applications of chlorimuron had an influence on the incidence of TSWV in peanut (Prostko et al 2009). In other peanut research, applications of diclosulam (PPI), flumioxazin (PRE), imazapic (POST), paraquat (POST), and 2,4-DB (POST) did not affect the incidence of TSWV (Bailey et al 2000;Faircloth and Prostko 2010;Tubbs et al 2010;Wilcut et al 2001). The mechanism of how certain herbicides influence TSWV in peanut has not yet been discovered.…”
Section: Resultsmentioning
confidence: 99%
“…None ofthe cultivars evaluated were negatively impacted « 5% visual injury and no yield reduction) by either imazapic or diclosulam applied at twice the labeled rate in any of the 3 yr of the study (data not shown). Previous research has indicated similar results (no effect on peanut yield) with diclosulam applied to virginia-type cultivars (Wilcut et al, 1997;Bailey et al, 1999Bailey et al, , 2000. Others have evaluated imazapic on viginia-, spanish-, and runner-type cultivars Wilcut et al, 1996;Dotray et al, 2001).…”
Section: Nonementioning
confidence: 89%
“…They reported some initial peanut injury from imazapic at 71 g/ha but no effect on yield. Bailey et al (2000) evaluated the tolerance of eight virginia market-type cultivars to diclosulam at 36 g/ha and observed~3% visual injury and no effect on peanut yield. Previous research with other herbicides has in some instances indicated differential cultivar response (]ohnson et al, 1992), while tolerance to other herbicides was independent of cultivar (Grichar and Colburn, 1993;Johnson et al, 1993).…”
mentioning
confidence: 99%
“…Johnson et al, (1993) reported there was no yield response of Florunner, NC 7, or Southern Runner to multiple herbicide applications, but canopy widths were affected. Diclosulam, an ALS-inhibiting herbicide like imazethapyr and imazapic did not affect growth, disease incidences, grade parameters, or yield in eight virginia peanut cultivars (Bailey et al, 2000).…”
mentioning
confidence: 88%